Mass Spectra Analyses of Amides and Amide Dimers of Steviol, Isosteviol, and Steviolbioside. (12th April 2012) - Lee, Lin-Wen; Lee, Tzong-Huei; Lin, Ching-Tung; Chen, Tiffany; Lin, Pen-Yuan
Abstract : The mass spectra of a series of stevioside analogues including the amide and dimer compounds of steviol, isosteviol, and steviolbioside were examined. Positive ion mass spectral fragmentation of new steviol, isosteviol, and steviolbioside amides and the amide dimers are reported and discussed. The techniques included their synthesis procedures, fast-atom bombardment (FAB), and LC/MS/MS mass spectra. Intense [M+H] + and [M+Na] + ion peaks were observed on the FAB and ESI spectra. LC/MS/MS also yielded ES+ and ES− ion peaks that fairly agreed with the results of the FAB and ESI studies. Mass spectral analysis of compounds4p-q, 5a-g, 6, and7 revealed the different cleavage pathway patterns that can help in identifying the structures of steviolbioside and its amide derivatives.